2020
DOI: 10.2147/ott.s245896
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comprehensive Transcriptomic Analysis and Experimental Validation Identify lncRNA HOXA-AS2/miR-184/COL6A2 as the Critical ceRNA Regulation Involved in Low-Grade Glioma Recurrence</p>

Abstract: Purpose: The recurrence and metastasis of glioma are closely related to complex regulatory networks among protein-coding genes, lncRNAs and microRNAs. The aim of this study was to investigate core genes, lncRNAs, miRNAs and critical ceRNA regulatory mechanisms, which are involved in lower-grade glioma (LGG) recurrence. Materials and Methods: We employed multiple datasets from Chinese Glioma Genome Atlas (CGGA) database and The Cancer Genome Atlas (TCGA) to perform comprehensive transcriptomic analysis. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Our result also showed that NPC2 independently indicated unfavorable prognosis in glioma when adjusted for with patents’ age ( p value = 0.04) and alive status ( p value = 0.039) ( Table 1 ), which revealed that NPC2 was a robust independent factor for predicting GBM survival. Considering that age has been identified as prognostic factors for GBM ( Chen P. et al, 2020 ; Hao et al, 2020 ; Zheng et al, 2020 ), NPC2 might be a prognostic marker of GBM based on its significant positive correlation with this disease. Hence, we focus on investing the clinical prognostic significance of the NPC2 genes in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Our result also showed that NPC2 independently indicated unfavorable prognosis in glioma when adjusted for with patents’ age ( p value = 0.04) and alive status ( p value = 0.039) ( Table 1 ), which revealed that NPC2 was a robust independent factor for predicting GBM survival. Considering that age has been identified as prognostic factors for GBM ( Chen P. et al, 2020 ; Hao et al, 2020 ; Zheng et al, 2020 ), NPC2 might be a prognostic marker of GBM based on its significant positive correlation with this disease. Hence, we focus on investing the clinical prognostic significance of the NPC2 genes in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that, through the regulation of ADAM12, SP1-mediated upregulation of lncRNA LINC01614 functions as a ceRNA for miR-383, thereby facilitating glioma progression (22). Using a comprehensive transcriptomic analysis and experimental validation, Chen et al identified lncRNA HOXA-AS2/miR-184/COL6A2 as the critical ceRNA regulatory complex involved in low-grade glioma recurrence (23).…”
Section: Discussionmentioning
confidence: 99%
“…HOXA-AS2 is a novel cancer-related lncRNA that has been demonstrated to be aberrantly expressed in various cancer types (62)(63)(64). In TC, the expression of HOXA-AS2 is upregulated in PTC tissues (65).…”
Section: Hoxa Cluster Antisense Rna2 (Hoxa-as2)mentioning
confidence: 99%